CERVICAL CANCER: WOMAN’S PERCEPTION REGARDING SELF-CARE - Darlly Vieira Dos Santos, Mayza; Erika Abrantes Coutinho, Vanessa; Caroline de Souza, Anne; Silva Oliveira, Geane (Health and Society, 2023)
The study aimed to verify women’s perception regarding the prevention and self-care of uterine cancer. This is an integrative review of the literature, in which the research was carried out between March and October 2023, through databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Science Health (LILACS) and Nursing Database (BDENF). Subsequently, the inclusion and exclusion criteria were used, 16 studies were selected. The present research showed that women’s perception is associated with feelings of fear, shame, not having enough knowledge about the prevention of cervical cancer, which is also linked to the sociodemographic profile. However, knowledge about cervical cancer is extremely important in adhering to the exam, emphasizing the need for women’s health education in the form of prevention and self-care of neoplasia and, consequently, through the prevention of cervical cancer, the risk of number of morbidity and mortality through early diagnosis.